A Dendritic Polymer‐Based Nanosystem Mediates Drug Penetration and Irreversible Endoplasmic Reticulum Stresses in Tumor via Neighboring Effect. Issue 20 (11th April 2022) - Zheng, Xiuli; Pan, Dayi; Zhu, Guonian; Zhang, Lu; Bhamra, Apanpreet; Chen, Rongjun; Zhang, Hu; Gong, Qiyong; Gu, Zhongwei; Luo, Kui
Abstract: Nanoparticles (NPs)‐based cancer therapeutics are generally impeded by poor drug penetration into solid tumors due to their dense tumor extracellular matrix (ECM). Herein, pH/redox‐responsive dendritic polymer‐based NPs are developed to amplify the neighboring effect for improving drug penetration and driving cell apoptosis via combination therapy. Pyropheophorbide a (Ppa) is conjugated with PEGylated dendritic peptides via disulfide bonds and doxorubicin (DOX) encapsulated in the conjugate to construct dual‐responsive NPs, PDPP@D. Delayed released DOX and Ppa from PDPP@D exert their combination therapeutic effect to induce cell apoptosis, and then they are liberated out of dying cells to amplify the neighboring effect, resulting in their diffusion through the dense ECM and penetration into solid tumors. Transcriptome studies reveal that PDPP@D leads to irreversible stress on the endoplasmic reticulum and inhibits cell protection through blocking the IRE1‐dependent survival pathway and unleashing the DR5‐mediated caspase activity to promote cell death. The strategy of amplifying the neighboring effect of NPs through combination therapy may offer great potential in enhancing drug penetration and eradicating solid tumors. Abstract : A versatile strategy based on dual‐responsive nanosystem for combination therapy is developed to promote drug penetration in tumors through amplifying the neighboring effect, which may shed light on overcoming the tumor extracellular matrix barrier and eradicating solid tumors.